Agrowastes as Feedstock for the Production of Endo-β-Xylanase from Cohnella sp. Strain AR92 - Pisa, José Horacio (2017)
Members of Cohnella sp. isolated from a variety of environments have been shown to be glycoside hydrolase producers. Nevertheless, most evaluations of members of this genus are limited to their taxonomic description. The strain AR92, previously identified as belonging to the genus Cohnella, formed a well-supported cluster with C. thailandensis and C. formosensis (>80% bootstrap confidence). Its growth and xylanase production were approached by using a mineral-based medium containing alkali-pretreated sugarcane bagasse as the main carbon source, which was assayed as a convenient source to produce biocatalysts potentially fitting its degradation. By means of a two-step statistical approach, the production of endoxylanase was moderately improved (20%). However, a far more significant improvement was observed (145%), by increasing the inoculum size and lowering the fermentation temperature to 25°C, which is below the optimal growth temperature of the strain AR92 (37°C). The xylanolytic preparation produced by Cohnella sp. AR92 contained mild temperature-active endoxylanase (identified as redundant GH10 family) for the main activity which resulted in xylobiose and xylo-oligosaccharides as the main products from birchwood xylan.